PENGARUH SELF EFFICACY DAN LINGKUNGAN KERJA TERHADAP KOMITMEN ORGANISASIONAL (STUDI PADA KARYAWAN PT. SARANA PATRA JATENG) - Ica Arim Tiana, 13.05.51.0153; Priyono, Bambang Suko (Students' Journal of Economic and Management, 2019)
The purpose of this study was to determine the effect of self efficacy and work environment to organizational commitment of employee PT. Sarana Patra Jateng. Types of data used are primary data is obtained directly from the original source in the from questionnaire. Population in this research is employees of PT. Sarana Patra Jateng. Sampling was done by saturated sample with a total sample of 82 respondents. The data collected were analyzed using factor analysis to test the validity of the question items, the reliability testing using cronbach alpha and hypothesis testing using t test. The test result obtained that there is a positive and significant influence of self efficacy on organizational commitment and there is a positive and significant influence of work environment on organizational commitment.